EXPLORATION ON THE DEFINITION AND THE REAL MEANING OF CORPORATE REAL ESTATE TERM - Fadzil, Farahiyah (PLANNING MALAYSIA, 2019)
Corporate Real Estate (CRE) is not a new term in the field of property research. In fact, disciplines of CRE research are becoming increasingly widespread nowadays. Consequently, the interpretation of CRE term has undergone a paradigm shift as time goes by. This study explored the definitions of CRE in the eyes of academicians and researchers as well as the meanings of CRE based on Malaysian Accounting Standard Board (MASB). Literatures were chosen to illustrate the breadth of knowledge available regarding the CRE definition. The broad definition of Corporate Real Estate (CRE) term (since 1983 to 2016) has been presented in the form of table. The discussion on the definition of CRE involves four phases, where each phase consists of 10 years. This allowed the researcher to see whether there were any changes or improvements to the definition of CRE in the last 40 years. Then, the CRE meaning was further examined, but from a different perspective. Therefore, content analysis of annual reports prepared by 40 Malaysian non-property public listed companies was conducted in order to identify the CRE term that has been applied in their companies. It was found that the CRE term was not adopted to represent real estate of a particular company. This study managed to identify 29 different terms that represent corporate real estate assets, of which nine (9) are used to represent “building” while six (6) are used to represent “land”. However, to understand the CRE of a company, the terms used in the company annual report are insufficient. What is more important is to recognise the information related to the CRE asset value. The information is not only intended to illustrate the wealth of company CRE assets, but also to pinpoint anything that happens to CRE such as depreciation, disposal, etc.